Finding the Best Length of Video-Podcasts: Effects of Varied numbers of Video-Podcast Used on Listening Comprehension of Saudi Undergraduates - Shahid, Shahid Hussain; Zuraina, Ali (Novelty Journals, 2017)
Integration of video-podcasts has effectively promoted listening comprehension but its suitable length is yet to be known. The main objective of the present study is to identify the difference between the varied number of video-podcasts used and students’ performance in listening comprehension. The study investigated the effects of video-podcasts integration on listening comprehension from the perspective of varied number of Video-Podcasts used in instructions. The twelve-week quantitative study employed a quasi-experimental pre-test post-test design. A total of 120 samples included in a control and three experimental groups. ANOVA analysis revealed an overall significant difference amongst the four groups. All the three experimental groups outperformed the control group. However, no significant difference was found between the control group and the 5 video-podcast group; and between 10 and 15 video-podcasts groups. The significant difference, however, was noted when the control group was compared to 10 and 15 video-podcast groups. Similarly, the difference between 5 and 10 video-podcast groups; and between 5 and 15 video-podcast groups was also significant. The findings imply that video-podcasts are useful resource for enhancing EFL learners’ listening comprehension. However, their appropriate length needs to be considered for the desired results.